Cyto-histological correlation of 219 patients submitted to surgical treatment due to diagnosis of cervical intraepithelial neoplasia - Adad, Sheila Jorge; Souza, Maria Azniv Hazarabedian; Etchebehere, Renata Margarida; Saldanha, João Carlos; Falco, Vera Alice Aguiar; Murta, Eddie Fernando Cândido (São Paulo Medical Journal, 1999)
CONTEXT: Cervical cytology continues to be the most appropriate method for investigating cervical neoplasia and its precursors. Greater diagnostic acuity is obtained by combining cytology, colposcopy and guided biopsy methods. OBJECTIVE: To analyze the diagnostic acuity of cyto- and histopathological exams and causes of diagnostic error. DESIGN: Retrospective study. SETTING: A public tertiary referral center. SAMPLE: Reports on 219 patients submitted to cone biopsy and/or hysterectomy due to diagnosis of cervical intraepithelial neoplasia (CIN) in the period between January 1982 and March 1997 were reviewed, comparing. MAIN MEASUREMENTS: cytological and histological exams (guided biopsy and surgically-removed tissue). In cases of discordance, the cyto- and histological preparations were reviewed to try to evaluate the causes of errors. RESULTS: In 193 cases (88.1%) there was cyto-histological agreement but none in 26 (11.9%). Review of the discordant cases showed that in 2 (0.9%) there was invasion of the stromata to a depth greater than 3mm, and in 7 (3.2%) microinvasion, unsuspected via cytology; in 2 (0.9%) microinvasion was suspected via cytology but not confirmed by the final histological exam; and in 15 (6.8%) there was disagreement about the degree of CIN. CONCLUSION: The principal causes of error in the cytological exam were the lack of reliable morphological criteria for microinvasion, absence of sampling of the squamocolumnar junction, and scarcity of neoplastic cells in the sample. As for the histological exam, the errors were related to inadequate technical processing and underestimation of focal lesions.